Recommending Words Using a Bayesian Network - Santos, Pedro (2023)
Funding Information: This work was supported by the REV@CONSTRUCTION mobiliser project, under the grant LISBOA-01-0247-FEDER-046123 from ANI (National Innovation Agency), with financial support from FCT (Fundação para a Ciência e a Tecnologia), through national funds. This work contributes to the Strategic Research Plan of the Centre for Marine Technology and Ocean Engineering (CENTEC), which is financed by FCT under contract UIDB/UIDP/00134/2020. Publisher Copyright: © 2023 by the authors.